Natal and breeding dispersal in the Baltic Greylag Goose Anser anser - Nilsson, L; Persson, H (Wildfowl, 2001)
Dispersal from the center of the breeding range of the Baltic Greylag-Goose Anser anser was studied using observations of individuals with neck collars. The median natal dispersal distance was 0 km in females and 25 km in mates, respectively. All of the females recruited to within 7 km of where they had been reared, 87% to the natal lake and 11% to neighboring water bodies. Of the males, only 11% recruited to the natal lake, while one individual was found more than 1,000 km from its place of birth. Even though the males dispersed to a greater distance within the population's breeding range, their distribution was still highly skewed towards their point of origin. Two thirds of all mates recruited within 30 km of the site where they had been reared. Once recruited, both sexes exhibited an extremely strong philopatry to their breeding area. Only 1.5% of the males and 0.5% of the females changed breeding site between successive years. All breeding dispersal occurred within the local population, and in no case exceeded 6 km.